2020
DOI: 10.1039/d0sm01244k
|View full text |Cite
|
Sign up to set email alerts
|

Tuning fullerene miscibility with porphyrin-terminated P3HTs in bulk heterojunction blends

Abstract: Porphyrin-terminated P3HTs represent an example of molecular engineering, where π-stacking interactions with the porphyrin enhance fullerene miscibility in BHJ blends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…By adjusting the miscibility between donor and acceptor, the content of the blend phase can be adjusted. 72,[87][88][89][90][91][92][93][94][95] Miscibility is an intrinsic property of the material. Usually, good miscibility between the donor and acceptor would induce more content of intermixed phase.…”
Section: Regulating the Content Of Intermixed Phasementioning
confidence: 99%
“…By adjusting the miscibility between donor and acceptor, the content of the blend phase can be adjusted. 72,[87][88][89][90][91][92][93][94][95] Miscibility is an intrinsic property of the material. Usually, good miscibility between the donor and acceptor would induce more content of intermixed phase.…”
Section: Regulating the Content Of Intermixed Phasementioning
confidence: 99%
“…Conjugated polymers (CPs) have been widely used in a variety of organic electronic devices including organic transistors, light-emitting diodes, solar cells, and sensors. The performance of organic electronic devices is strongly dependent on the intermolecular morphologies of CPs such as translational and orientational orderings. In particular, the liquid crystalline (LC) characteristics of CPs, arising from rod-like π-conjugated anisotropic shapes, have provided an effective way to achieve a long-range oriented molecular arrangement with effective charge transport. These highly aligned self-assembled structures can be effectively obtained from the LC phase by reducing the energy barrier for crystal nucleation and coil-to-rod transitions during solution processing. For example, LC characteristics have been reported in several CPs such as poly­(2,5-bis­(3-tetradecylthiophen-2yl)­thieno­(3,2- b )­thiophene) (PBTTT), poly­(3-hexylthiophene) (P3HT), and poly­[3-(potassium-7-hexanoate)-thiophene-2,5-diyl] (P3PHT), significantly enhancing electrical performances by manipulating their LC structures. , Therefore, precise control of LC interaction, which determines the liquid crystalline behavior of rod-like polymers, has been considered crucial for achieving long-range ordering of CPs. However, it is still challenging and requires a fundamental understanding of the LC characteristics of the CPs. , …”
Section: Introductionmentioning
confidence: 99%
“…One method to stabilize device morphology is to add a compatibilizer as a third component into the active layer blend. , The compatibilizer localizes at the interface between immiscible phases, lowers the interfacial tension, and increases the interfacial adhesion. , Both small molecules and polymers have been used to stabilize domain sizes in active layer blends. In our previous work, we used a fullerene-functionalized P3HT copolymer to stabilize P3HT:PC 61 BM blend morphologies .…”
Section: Introductionmentioning
confidence: 99%
“…We found that a random copolymer with 20 mol % fullerene-functionalized side chains at 8 wt % in the blend was best at preventing micron-scale phase separation in annealed thin film blends and OPVs. In our work, and in other examples, 32,36,38,39,44 tailored compatibilizers were synthesized to match the specific donor and acceptor in the active layer of the OPV. Synthesizing custom compatibilizers is time-intensive and impractical for complex donor polymers.…”
Section: ■ Introductionmentioning
confidence: 99%